“Speaking Out of the Most Passionate Love” – James Baldwin and Pragmatism - Ulf Schulenberg (European Journal of American Studies)
This article seeks to contribute to a discussion of pragmatism’s political impulses. It concentrates on the hitherto somewhat neglected question of pragmatism and race. In order to elucidate one possibility of approaching this complex question, the article discusses James Baldwin’s essays. It is argued that Baldwin’s essays can be used to show the significance of a middle ground between Cornel West’s prophetic pragmatism and Richard Rorty’s liberal version of neopragmatism. While the first part analyzes West’s prophetic and worldly pragmatism, the second part seeks to illuminate Rorty’s notion of a pragmatist literary or poeticized culture. The final part demonstrates that while it would be pointless to claim that Baldwin is a radically postmetaphysical author and thus an ideal member of a literary culture, his politicized version of self-creation makes it seem legitimate to advance the argument that he is part of a left-liberal tradition of worldly pragmatism that sees the work of the strong poet or creative redescriber as contributing to political and social change.